The Great Snake Escape - Coxe, Molly (USA : Harper Collins, 1994)
Mirabel, a goose, and her friend Maxie, a frog, get a scare one day when a king cobra escapes from the zoo.
Keywords: Geese -- Fiction; Snakes -- Fiction; Frogs